A Prussian blue/carbon dot nanocomposite as an efficient visible light active photocatalyst for C–H activation of amines. Issue 10 (12th September 2016) - Maaoui, Houcem; Kumar, Pawan; Kumar, Anurag; Pan, Guo-Hui; Chtourou, Radouane; Szunerits, Sabine; Boukherroub, Rabah; Jain, Suman L.
Abstract : Prussian blue/carbon dot (PB/CD) nanocomposite was found to be a visible light active photocatalyst for the oxidative cyanation of tertiary amines using NaCN/AcOH as cyanide source and H2 O2 as an oxidant. Abstract : A Prussian blue/carbon dot (PB/CD) nanocomposite was synthesised and used as a visible-light active photocatalyst for the oxidative cyanation of tertiary amines to α-aminonitriles by using NaCN/acetic acid as a cyanide source and H2 O2 as an oxidant. The developed photocatalyst afforded high yields of products after 8 h of visible light irradiation at room temperature. The catalyst was recycled and reused several times without any significant loss in its activity.